12(g-9)=60

Simple and best practice solution for 12(g-9)=60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12(g-9)=60 equation:


Simplifying
12(g + -9) = 60

Reorder the terms:
12(-9 + g) = 60
(-9 * 12 + g * 12) = 60
(-108 + 12g) = 60

Solving
-108 + 12g = 60

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '108' to each side of the equation.
-108 + 108 + 12g = 60 + 108

Combine like terms: -108 + 108 = 0
0 + 12g = 60 + 108
12g = 60 + 108

Combine like terms: 60 + 108 = 168
12g = 168

Divide each side by '12'.
g = 14

Simplifying
g = 14

See similar equations:

| 33=x^2+999 | | C+4*4=-13.66 | | (3)6= | | y=7x+275 | | 580=9m | | 4(g-5)+9g= | | 3(8)= | | 80=4x-7(4x+16) | | 9x+15=17x-7 | | 5x+2x+3=-6x+12+13x | | 9t+3t=144 | | x+4x-5=0 | | 1.79+1.19(10-x)=16.10 | | 5-(6k+1)=2((5k-3)-(K-2)) | | (10+4(-5)-6)= | | 7w-16=37 | | -p+14p-16p+7=-11 | | 143+2h=1013 | | 24x^4+16x^3+16x^2+8=0 | | 3(k+5)=45 | | -3(.83x+.6)=1.75 | | 945=5(x+17) | | 5x^2+5y^2-6y=0 | | 2x+40=88 | | 0.5(6x+4)=12 | | 9x-34=9x+33 | | 2x+8y=62 | | 6t-8=t+7 | | 11x-(x+7)=3 | | -8(4-r)=16 | | r/7+2=6 | | 0.5(12x-14)=11 |

Equations solver categories